Islam In America: By Jane 1 Smith. (New York: Columbia University Press, 1999. 251 pages.) (American Journal of Islam and Society, 2002)
Written by a professor oflslamic Studies at Hartford Seminary in Connecticut,ls/am in America introduces the history and practice of Islam in theUnited States. The book opens with an overview of the origins and historicaldevelopment of Islam that for the most part is fair, although there is theodd error ("Throughout the centuries, the call to prayer has been sung ..."Some of the figures mentioned in Chapter 2, "Contributors to the Developmentof Islam" also cause eyebrows to be raised: how much the secularistMustafa Kemal contributed to the development oflslam is surely debatable.Moving on to the American context (Chapter 3), the author starts herexploration oflslamic history in the US with the waves of immigration fromMuslim lands that began in the middle and latter part of the nineteenth century. Pre-Columbian visits to these shores by Muslims are touched upon, butit is noted that this is a new area of scholarship. The issue of Muslim slavesbrought by force from Africa is dealt with later, in the chapter on AfricanAmericanIslam.The issues faced by the earliest immigrants are touched upon, and abrief history oflslam in several major centers is given. Accounts of minoritygroupings - Sh????a, Sufis, Isma>il is, Druze, and Ahmad is- are also given.Whether all of these groupings are "truly Islamic" or not is a moot point,however, the fact that they are connected to or have roots in the Islamic traditionmeans that they are often included in studies of Islam, particularlystudies written by western observers. While stating that the majority ofMuslims in the US are either immigrants or African-Americans, the authornotes that there are significant numbers of converts from other backgroundstoo; mention is made of Anglos, Hispanics and Native Americans who havecome to Islam ...